Cell-cycle dependent phosphorylation of yeast pericentrin regulates γ-TuSC-mediated microtubule nucleation - Lin, Dennis Tien-chen; Neuner, Annett; Schlosser, Yvonne T; Scharf, Annette N. D.; Weber, Lisa; Schiebel, Elmar (eLife, 2014)
Budding yeast Spc110, a member of γ-tubulin complex receptor family (γ-TuCR), recruits γ-tubulin complexes to microtubule (MT) organizing centers (MTOCs). Biochemical studies suggest that Spc110 facilitates higher-order γ-tubulin complex assembly (). Nevertheless the molecular basis for this activity and the regulation are unclear. Here we show that Spc110 phosphorylated by Mps1 and Cdk1 activates γ-TuSC oligomerization and MT nucleation in a cell cycle dependent manner. Interaction between the N-terminus of the γ-TuSC subunit Spc98 and Spc110 is important for this activity. Besides the conserved CM1 motif in γ-TuCRs (), a second motif that we named Spc110/Pcp1 motif (SPM) is also important for MT nucleation. The activating Mps1 and Cdk1 sites lie between SPM and CM1 motifs. Most organisms have both SPM-CM1 (Spc110/Pcp1/PCNT) and CM1-only (Spc72/Mto1/Cnn/CDK5RAP2/myomegalin) types of γ-TuCRs. The two types of γ-TuCRs contain distinct but conserved C-terminal MTOC targeting domains., DOI: - http://dx.doi.org/10.7554/eLife.02208.001, Microtubules are hollow structures made of proteins that have a central role in cell division and a variety of other important processes within cells. For a cell to divide successfully, the chromosomes containing the genetic information of the cell must be duplicated and then separated so that one copy of each chromosome ends up in each daughter cell. To separate the chromosomes, microtubules extend out from two structures called spindle pole bodies, which are found at either end of the cell, and pull one copy of each chromosome to opposite sides of the cell., Although the individual proteins that make up a microtubule can self-assemble into tubes, this occurs very slowly, so cells employ other molecules to speed up this process. In yeast cells, a protein called gamma-tubulin is recruited to the spindle pole body by the protein Spc110, where it combines with two other proteins to form a complex called the gamma-tubulin small complex. Several of these complexes then join together to form a ring, which probably acts as the platform that microtubules grow from. Recent observations suggested that Spc110 may help to construct this ring, but without revealing how., Now, Lin et al. reveal that Spc110 can regulate microtubule formation by controlling how several gamma-tubulin small complexes bind together, and have identified the exact section of Spc110 that interacts with the complexes. However, the Spc110 must become active before it can perform this role, and it is only activated during certain stages of cell division, through phosphorylation. The structures in Spc110 that bind to the gamma-tubulin small complex in yeast are also found in gamma-tubulin binding receptor proteins in human cells. The work of Lin et al. demonstrates that proteins that are assumed to have passive roles within cells, such as Spc110, often play more active roles instead., DOI: - http://dx.doi.org/10.7554/eLife.02208.002
Gesehen am 18.02.2021